2015
DOI: 10.17116/terarkh2015875122-126
|View full text |Cite
|
Sign up to set email alerts
|

Role of animal gastric Helicobacter species in human gastropathology

Abstract: Род Helicobacter семейства Helicobactеraceae объединяет под-вижные (лофо-или амфитрихи), грамотрицательные, каталазо-и оксидазоположительные, преимущественно спиралевидные бак-терии, не образующие спор. Первоначально бактерии относили роду Campylobacter, но после выяснения их биохимических осо-бенностей, в 1989 г. хеликобактеры (ХБ) классифицированы в от-дельный род. Более того, позднее некоторые кампилобактеры перенесены в состав рода Helicobacter. Природными хозяевами бактерий являются различные животные и ч… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
0
0
1
Order By: Relevance
“…It is concluded that 86.6% of the felines presented colonization by Helicobacter spp, and that the rapid urease test constitutes a reliable method for the diagnosis of infection by Helicobacter spp. Estudios epidemiológicos han demostrado una relación entre el contacto con los animales y el estado de colonización o infección por Helicobacter spp a humanos (Shojaee Tabrizi et al, 2015; Smet et al, 2018), por lo que actualmente existe una creciente preocupación por el potencial rol zoonótico de estas bacterias (Pozdeev et al, 2015). En este contexto, es importante contar con métodos diagnósticos que permitan resultados rápidos y confiables.…”
Section: Introductionunclassified
“…It is concluded that 86.6% of the felines presented colonization by Helicobacter spp, and that the rapid urease test constitutes a reliable method for the diagnosis of infection by Helicobacter spp. Estudios epidemiológicos han demostrado una relación entre el contacto con los animales y el estado de colonización o infección por Helicobacter spp a humanos (Shojaee Tabrizi et al, 2015; Smet et al, 2018), por lo que actualmente existe una creciente preocupación por el potencial rol zoonótico de estas bacterias (Pozdeev et al, 2015). En este contexto, es importante contar con métodos diagnósticos que permitan resultados rápidos y confiables.…”
Section: Introductionunclassified